CRITICAL DISCOURSE ANALYSIS: SUBMITTING THE NEWS ABOUT BORIS JOHNSON'S VICTORY IN THE ELECTION OF ENGLAND PRIME MINISTER THROUGH ONLINE MEDIA - Rahmayani, Fitri Ana (jfpublisher, 2022)
Nowadays, information delivery often relies on internet-based media, also known as online media. This study aims to examine how Boris Johnson's victory in the British Prime Minister election is reported through the electronic media Liputan6.com and to analyze the critical discourse meaning of its coverage in CNN Indonesia. This research employs a qualitative descriptive method and utilizes Fairclough's discourse analysis. Fairclough emphasizes